Adverse events in nursing: A retrospective study of reports of patient and relative experiences. (24th June 2015) - Andersson, Å.; Frank, C.; Willman, A.M.L.; Sandman, P.‐O.; Hansebo, G.
<x xml:space="preserve">Abstract</x> Background Patient safety is an important global issue. While it is well known that patients can suffer from adverse events in nursing care, there is a lack of knowledge as to how they experience them. Aim To examine adverse events in nursing care as they are experienced by patients and relatives. Methods This was a retrospective study taking both a qualitative and a quantitative approach. It was based on data regarding 242 adverse events in nursing care, as reported by patients and relatives to Sweden's Medical Responsibility Board, content analysis was used to analyse the reports. Results Patients' and relatives' experiences were analysed into four categories of adverse events, as concerning participation, clinical judgement, nursing intervention and the essentials of care. Limitations The reports were classified by the Medical Responsibility Board, without a standardized system. The adverse events reported were few in number and were reported by patients and relatives only. Conclusion Lack of participation has negative consequences and contributes to adverse events. Adverse events occur through missed care as well as through carer errors. Implications on nursing and health practice Nurses need to improve their skills that support patient participation. Patient participation needs to be incorporated into nurses' duties. Implications for Nursing and Health Policy Resources for patients to participate in their own care needs to be a priority underpinning policy‐making in health systems. Nursing education systems need to teach students about the value and benefits of involving patients in their care.